ELECTROCHEMICAL BEHAVIOR OF GOLD-SILVER ALLOYS IN HYDROCHLORIC ACID SOLUTIONS: EFFECT OF SILVER CONCENTRATION - Зиядуллаев Абдукаххар Шамсиевич; Медведев Александр Жанович (Journals Park Publishing, 2024)
The effect of silver (up to 20 % by weight) on the kinetics of anodic dissolution of gold-silver alloys in hydrochloric acid solutions was studied by the method of potentiostatic inclusion curves. It is shown that the dependence of current density on time can be consistently described by models of formation and thickening of a porous film of silver chloride. Introduction: scrap from jewelry refineries, lead scrap, dentures, special solders, etc. is a potential source of additional increase in the production of non-ferrous and precious metals in the Republic of Uzbekistan. The development of a technology for purifying such non-ferrous and other valuable metals from secondary raw materials is an urgent problem. Objects and methods of research. Gold-silver alloys (with a silver content of 4 to 20% by weight) in the form of cylinders with a diameter of about 1 mm were prepared from weights of pure (99.99%) gold and silver by melting under vacuum in a special graphite container and holding the melt for 3-5 hours. as well as anodic polarization curves were recorded using the RA-3 polarograph. Results and discussion. On the anodic polarization curve of pure gold in chloride solutions (Fig. 1, curve 1) in the region of overvoltages η = 300-600 mV There is a stationary zone of active dissolution with a clearly defined limiting current. The value of this current is proportional to the chloride concentration [3] and the square root of the potential sweep velocity, i.e. it is the limiting diffusion current for Cl anion-. With further anodic polarization, the gold surface is passivated by a film of oxides, followed by the release of chlorine. Objective: to study the effect of silver on the kinetics of anodic dissolution of gold-silver alloys in chloride solutions.
Keywords: alloys, electrochemical dissolution, anode, cathode, current density, potential.